Kesalahan Siswa dalam Menyelesaikan Soal Sistem Persamaan Linear Dua Variabel Tipe HOTS Ditinjau dari Gaya Kognitif di Masa Pandemi Covid-19 - Afinda Azimatul Khusna; Rizky Esti Utami; Farida Nursyahidah (Jurnal Tadris Matematika, 2021)
This research aimed to describe errors done by students in solving HOTS typed linear equation of two variables problem seen from the cognitive style in a Covid-19 pandemic era. This research uses a qualitative approach. Research subjects consist of 4 students selected among 31 students from class IX Junior High School 1 Petarukan, grouped into two students with cognitive style field-dependent (FD) and two students with cognitive style field-independent (FI). Subjects cognitive style was determined by Group Embedded Figures Test (GEFT) score, while errors in problem-solving were determined through TKPS and interviews. Field-dependent subjects tend to make errors in transformation and encoding with low or fair fallacy rate. On the other side, field-independent subjects tend to make errors in understanding the problems with low fallacy rate. The causes of errors made by field-dependent subjects are not being able to make complete mathematical models and not showing what they had searched. Meanwhile, field-independent subjects were incapable of making sketches perfectly. Other researchers' recommendation explains only errors in reading, transformation, processing capability, and encoding of students with cognitive style FD and FI. In this context, there are still a lot of other errors done by students. Therefore, the next researcher needs to conduct further research with better execution.